Finding Constellations in Chemical Space Through Core Analysis - Naveja, J. Jesús; Medina-Franco, José L. (Frontiers in Chemistry, 2019)
Herein we introduce the constellation plots as a general approach that merge different and complementary molecular representations to enhance the information contained in a visual representation and analysis of chemical space. The method is based on a combination of a sub-structure based representation and classification of compounds with a “classical” coordinate-based representation of chemical space. A distinctive outcome of the method is that organizing the compounds in analog series leads to the formation of groups of molecules, aka “constellations” in chemical space. The novel approach is general and can be used to rapidly identify, for instance, insightful and “bright” Structure-Activity Relationships (StARs) in chemical space that are easy to interpret. This kind of analysis is expected to be especially useful for lead identification in large datasets of unannotated molecules, such as those obtained through high-throughput screening. We demonstrate the application of the method using two datasets of focused inhibitors designed against DNMTs and AKT1.